Inland navigation: PAH inventories in soil and vegetation after EU fuel regulation 2009/30/EC - Bläsing, M.; Amelung, W.; Schwark, Lorenz; Lehndorff, E. (Elsevier, 2017)
© 2017 Elsevier B.V.In January 2011, fuel quality in inland water vessels was changed by EU regulation 2009/30/EC, aiming at improving air quality along waterways. We hypothesized that the implementation of this regulation both lowered the total deposition of polycyclic aromatic hydrocarbons (PAHs) and changed their composition in river valleys. We analyzed parent-, alkylated- and thio-PAHs in soil and vine leaves, at two waterways (Rhine and Moselle, Germany), as well as in one ship-free reference area (Ahr, Germany). Samples were taken annually (2010–2013) in transects perpendicular to the rivers. We did not find any relation of PAH concentration and composition on vine leaves to inland navigation, likely because atmospheric exchange processes distorted ship-specific accumulation patterns. We did find, however, an accumulation of ship-borne PAHs in topsoil near the waterways (1543 ± 788 and 581 ± 252 ng g- 1 at Moselle and Rhine, respectively), leading to larger PAH concentrations at the Moselle Valley than at the reference area (535 ± 404 ng g- 1) prior to EU fuel regulation. After fuel regulation, the PAH concentrations decreased in topsoils of the Moselle and Rhine Valley by 35 ± 9 and 62 ± 28%, respectively. These changes were accompanied by increasing proportions of dibenzothiophene (DBT) and low molecular weight PAHs. Both, changes in PAH concentrations and composition were traceable within 200 and 350 m distance to the river front of Moselle and Rhine, respectively, and likely favored by erosion of topsoil in vineyards. We conclude that the EU regulation was effective in improving soil and thus also air quality within only three years. The impact was greater and spatially more relevant at the Rhine, which may be attributed to the larger traffic volume of inland navigation.